Ti0·33Al0.67 cathode surface modifications and the effect on the mechanical and electrochemical properties of AlTiN coating. (September 2016) - Xu, Yinchao; Chen, Kanghua; Wang, Shequan; Pan, Chenxi; Chen, Songyi
Abstract: Ti0·33 Al0.67 target is widely applied in cathodic arc evaporation deposition for preparing hard coating. The morphology, composition and organizational structure of eroded Ti0·33 Al0.67 target were analyzed by scanning electron microscope/energy disperse spectroscopy (SEM/EDS), x-ray photoelectron spectroscopy (XPS) and x-ray diffractometer (XRD). Inhomogeneous converted layers with Alx Tiy intermetallic and (Ti, Al) N nitride formed on the top of eroded cathode while micro-holes and cracks appeared on the surface of eroded cathode. The morphology, mechanical and electrochemical properties of AlTiN coatings deposited by virgin and eroded targets were researched. The results showed that the hardness, adhesive strength with the substrate and corrosion resistance of AlTiN coating deposited by the eroded target were all improved compared with that deposited by virgin target. It's demonstrated that improvements on the properties of the AlTiN coating caused by the eroded target should be attributed to lower macroparticles density and fewer defects in the coating. Highlights: Alx Tiy intermetallic and (Ti, Al) N nitride were on the surface of the eroded target. Fewer macroparticles in the surface of coating deposited by eroded cathode. The mechanical property of the coating deposited by eroded cathode is improved. The electrochemical property of the coating deposited by eroded cathode is improved.